1974
DOI: 10.2151/jmsj1965.52.5_417
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on Land and Sea Breezes in the Tokai Village Area

Abstract: Extensive observational programs on land and sea breezes were carried out by use of pibal method in the summer of 1971 and 1972 in the Tokai Village area facing the Pacific. Two pibal stations were set up at about one and six kilometers inland.Significant results obtained are as follows : (1) Vertical profiles of wind speed and direction in the lowest few hundred meters layer of the atmosphere in the sea breeze are significantly different between the coastal and the inland station, suggesting the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…We can clearly see the return current with respect to the oceanward wind and there is no return current with respect to the bayward wind. These features on the east coast are similar to those observed by Mizuma (1985). Next, we will show wind hodographs at several sites in Fig.…”
Section: Results and Discussion (A) Results For The Standard Baysupporting
confidence: 77%
See 1 more Smart Citation
“…We can clearly see the return current with respect to the oceanward wind and there is no return current with respect to the bayward wind. These features on the east coast are similar to those observed by Mizuma (1985). Next, we will show wind hodographs at several sites in Fig.…”
Section: Results and Discussion (A) Results For The Standard Baysupporting
confidence: 77%
“…It is important to examine the differences and their causes. Second, the ocean and Lo breezes are of considerable depths on the east coast (e.g., Mizuma, 1985). Namely, the depths of the ocean and Lo breezes are about 1100m and 800m, respectively, which are much greater than those of sea and land breezes observed in general (Hsu, 1970;Lyons, 1972;and many others).…”
Section: Introductionmentioning
confidence: 95%
“…Under clear-sky and calm conditions, this wind system, having a vertical scale of @1 km, will entirely cover the Kinki region from Kii Channel, from late afternoon to midnight (Itoh and Kawazoe 1983;Mizuma 1985). Itoh suggested that the relative locations of the Japan Sea and the Kii and Tsurugi mountain districts produced a large-scale horizontal pressure-gradient, which resulted in the formation of the extended seabreeze.…”
Section: The Extended Sea-breezementioning
confidence: 99%
“…For convenience, the northern portion of the Osaka plain, including the Kyoto basin area, is hereinafter referred to as the OsakaKyoto plain. The effects of the urban area on the structure and behavior of the local circulations in this region have not been well established, although observational and numerical studies were so far conducted by a number of researchers (e.g., Eguchi 1977;Mizuma 1995;Itoh 1995;Uno et al 1996). Ohashi and Kida (2001) observed the structure of the SBC over the northern Osaka urban area, and suggested that the deformation of the SBC was due to this urban area.…”
Section: Introductionmentioning
confidence: 99%
“…Visual inspection of the daily wind maps leads to the type classification of the diurnal variation of winds. Since there have been several observational studies of the L&SB in the coastal area of Osaka Bay (Itoh and Kawazoe, 1983;Mizuma, 1985), the behavior of the L&SB has been clarified to a considerable degree. Therefore, the occurrence of the L&SB can be easily determined on the daily wind map.…”
Section: Classification Of Land and Sea Breezes Typesmentioning
confidence: 99%